Experimental Modelling Studies on the removal of crystal violet, methylene blue and malachite green dyes using Theobroma cacao (Cocoa Pod Powder). - Daniel Omokpariola (Journal of Chemistry Letters)
The adsorption characteristics of basic dyes (crystal violet, CV), (methylene blue, MB) and (malachite green, MG) using Theobroma cacao (Cocoa pod powder), an alternative adsorbent were evaluated. Batch experiments were carried out by varying parameters such as pH, adsorbent dosage, contact time, initial dye concentration and temperature. The optimal conditions for the adsorption of CV, MB and MG on Cocoa pod powder, CCP were found have contact time (180 min), pH (4,8 and steady 6-10), temperature (333K) for an initial dye concentration of 60ppm using adsorbent dosage of 0.2g respectively. The adsorption capacity of CV, MB and MG dyes decreased with increasing CPP dosage, while there was increase with contact time and initial dye concentration. Eleven Isotherm parameters were tested with experimental data showed that CV, MB and MG dyes best fitted for Dubnin – Radushkevich, Langmuir and Freundlich isotherms. Adsorption Kinetic were modelled with Pseudo first-order, Pseudo second-order, Weber- Morris Intra-Particle diffusion, Boyd, Elovich, and Bangham. The data fitted well with Pseudo second order kinetic model compared to other kinetic models with correlation coefficient of 0.9933, 0.9981 and 0.9953 for CV, MB and MG dyes respectively. Thermodynamic parameter such as ΔG, ΔS and ΔH were calculated using van’t hoff’s and Arrhenius equations. The adsorption of CV, MB and MG increased with decreasing temperature as the process was exothermic, spontaneous and favourable in nature. Finally, the process parameter of each adsorption system is useful for developing environmental management and modelling matrices to understand best suitable system.